Learning to end: Trainee therapists’ experiences of imposed therapeutic Endings - Vernon, Jeremy; Schweitzer, Robert D. (European Journal for Qualitative Research in Psychotherapy, 2023)
The aim of the study was to explore trainee therapists’ experiences of imposing therapy endings with their clients. In this context, endings were imposed by the conclusion of training, as opposed to client needs. Following in-depth interviews with seven recently graduated psychologists, a thematic analytic approach was used to locate meaning within the participants’ dialogue and explicate themes embedded within the ending of therapy relationships during their training. Five categories of themes emerged from their experiences: saying goodbye as a performative experience; the experience of abandoning the other; the experience of we-ness; time as tyranny: we have no choice but to end; and experiencing the patient as mentor. From each of these five explicated categories, competencies relating to therapy endings are identified and articulated, and hopefully will serve to inform the teaching and learning of psychotherapy and the ending of therapy relationships, beyond imposed endings alone. The findings are particularly salient for trainee and early-career practitioners who may be working in contexts where endings are dictated by factors other than the needs of the patient.